Nagovor dekana red. prof. dr. Ivana Krajnca ob otvoritvi Medicinske fakultete Univerze v Mariboru 18. september 2013 / The speech of The dean and full-time professor Ivan Krajnc MD at the opening of the Faculty of Medicine of the University of Maribor on - Krajnc, Ivan (Acta Medico-Biotechnica, 2021)
Revered ladies, revered gentlemen! In the introduction allow me to thank you for having attended our ceremony in such a large number – for having attended the opening of the new building of the Faculty of Medicine of the University of Maribor. The joy is shared with us by our friends, our guests. Seven years have passed since we have, in our management of the Faculty of Medicine of the University of Maribor (MF UM), begun thinking also of our home. MF was operating on numerous locations, in the premises of the rectorate of the University of Maribor, in the premises of the University Clinical Centre of Maribor (UKC MB) and in the premises of the Institute of Public Health Maribor